THE DISCOURSE OF MUSLIM INTELLECTUALS AND `ULAMA’ IN INDONESIA: A Historical Overview (JOURNAL OF INDONESIAN ISLAM, 2010)
Muslim intellectuals and `ulama’ are two notions necessary for attempts to get deep understanding of particularly Indonesian Muslim scholars. This paper analyses the discourse of Muslim intellectuals and `ulama’ in Indonesia before the independence period. The focus is on the practices and vectors which paved the way for the Muslim intellectuals and `ulama’ to come to the forefront in socio-political and cultural arena of Indonesia. The paper argues that the emergence of Indonesian intellectuals was not only influenced by Muslim organisations but also by Study Clubs. It further argues that irrespective of the diverse identification of Muslims intellectuals, those with secular educational background dominated the public spehere of Indonesia in the pre-independence period than those trained in pesantren or traditional Islamic education. This codition was a result of the nexus of the colonial contribution through so-called ethical policy, the rise of socio-political and cultural association, and the emergence of study club, which gave rise to Muslim intellectuals with secular educational background.